2018
DOI: 10.46912/jbrcp.51
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and Outcome of Paediatric Long Bone Fractures Managed in a University Teaching Hospital

Abstract: Fractures constitute a significant component of paediatric trauma. Paediatric fractures account for significant morbidity. This study was set to elucidate the characteristics and outcome of paediatric fractures in a university teaching hospital. Case notes were reviewed for socio-demographic and clinical variables. Statistical analysis was carried out using the software Statistical Package for Social Sciences for Windows, Version 21.0. The correlation between development of complications and prior trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 16 publications
(23 reference statements)
1
5
1
Order By: Relevance
“…Our study showed involvement of the tibia, fibula, radius, and ulna, in descending order of occurrence. The predominance of tibial fractures in our study is similar to the other report by Omoke & Ekumankama in Abakiliki [24], and other locations [25,26]. However, it differs from another studies where the radius was commoner [27], and the femur in some other reports [28][29][30].…”
Section: Discussionsupporting
confidence: 85%
“…Our study showed involvement of the tibia, fibula, radius, and ulna, in descending order of occurrence. The predominance of tibial fractures in our study is similar to the other report by Omoke & Ekumankama in Abakiliki [24], and other locations [25,26]. However, it differs from another studies where the radius was commoner [27], and the femur in some other reports [28][29][30].…”
Section: Discussionsupporting
confidence: 85%
“…The reason for this may be due to the attempts at breaking the falls in such children. 20 This observation is different from the outcome of the study done in Enugu and Makurdi both in Nigeria which showed femur fracture and tibia fracture respectively as the most commonly fractured bones in children. Valerio et al and Agarwal in their study found that the distal radius was most commonly fractured bone.…”
Section: Discussioncontrasting
confidence: 61%
“…Other studies have also shown that fall is the most common cause of fractures in young people however previous study done in Nigeria by Elachi et al and Nwadinigwe et al showed that road traffic crash is the main cause of fracture. 9,11,20 The observation in our study may be due to the fact that most of our patients are below the age of ten years and at this stage of their development they want to explore their environment which may predispose them to falls. 20 Also, in developing countries, most parents go to work and leave their younger children (infants and toddlers) under the care of their elder siblings as such they become predispose to the incidence of falls.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations